Vulnerability and climate risk assessment in the Ecuadorian Amazon Region, based on ecological and socioeconomic infrastructures - Miguel Quishpe; Irene Acosta-Vargas; Adrian Buenaño; Bryan Rosero; Maria Reyes; Gustavo Duran; Rasa Zalakeviciute (Climate Risk Management)
Climate change is currently one of the greatest global concerns, as it increases the probability and magnitude of climate threats, putting population at risk, particularly in vulnerable regions such as the Ecuadorian Amazon Region (EAR). This area is known for its exceptional biodiversity and indigenous ethnic diversity but faces significant socioeconomic and environmental problems. The culturally diverse Amazonian tribes historically inhabit remote and difficult-to-access regions, which is reflected in low-level infrastructure and limited access to social services. These characteristics, combined with the lack of quantifiable data for the EAR, hinder the development of effective adaptation plans for climate hazards. To address this challenge, the present study evaluated climate risks under the current conditions and two Representative Concentration Pathways (RCPs) 4.5 and 8.5. The study followed the recommendations of the Intergovernmental Panel for Climate Change (IPCC) and Methods for the Improvement of Vulnerability Assessment (MOVE). Fuzzy logic was employed for the normalization and aggregation of multiple indicators classified under ecological and socioeconomic infrastructures. This approach allows the handling of scattered and complex information by generating partial or intermediate values, unlike classical logic, which is limited to binary outcomes (true or false). The main findings indicate that climate risk is high across the EAR in all scenarios, with particularly sever risks in the northern part of the region. Three consistent hotspots were identified in Lago Agrio, Shushufindi and Orellana, municipalities located within indigenous territories. This research provides a framework to support decision-making based on spatial analysis of climate-related information. We recommend incorporating ecological infrastructure into the development of holistic climate change adaptation plans, complementing traditional socio-economic assessments.